Histopathological Characteristics of Cutaneous Melanoma in Isfahan, Iran, from 2013 to 2018 - Zahra Malakoutikhah; Fatemeh Mohaghegh; Siavash Karimi; Parvin Rajabi; Elham T. Tabatabaei (Journal of Skin Cancer)
Objectives. To investigate the histopathological characteristics of cutaneous melanoma in Isfahan from 2013 to 2018, according to histopathological subtype, lesions location, Clark level, and Breslow thickness. Methods. A descriptive, retrospective study in reports of Alzahra Hospital and Dr. Rajabi Pathology Laboratory in Isfahan. Results. In total, 45 patients were included in this study. The most prevalent histopathological subtype was acral lentiginous melanoma (48.89%), followed by lentigo maligna melanoma (17.78%), nodular melanoma (11.11%), and superficial spreading melanoma (8.89%). Most malignant lesions were on the foot and toes (31.1%) and face (24.4%). Tumor invasion level was mainly at Clark level IV (42.2%). Furthermore, the mean depth of tumor penetration (Breslow thickness) was 3.87 ± 3.35. Conclusions. Our study revealed the characteristics of melanoma in the Iranian population. Our results showed a similar trend with previous studies in the Asian population. Further investigations are needed to elucidate the role of ethnic and environmental risk factors for developing melanoma in different populations.